Situation description and critical technology analysis for industrial connection of intelligent manufacturing - Jie LI; Dong ZHANG; Jie CHANG; Zhen YANG (Dianxin kexue)
With the formally issue of the industrial internet in USA,the industry 4.0 in German and made in China 2025,the integration of the IT,Internet and industrialization has became the trend of intelligent manufacturing.Industrial connection is the basic ability for intelligent manufacturing.Firstly,the technology situation of OT and IT industrial connection was described.And then combined with made in China 2025,the eight demands for industrial internet scenarios and industrial connectivity key technology were analyzed,including data acquisition,IP network,wireless network,identifier resolution and network security,Finally,according to the domestic situation,the future trend of industrial connection was prospected.